Evaluasi Kualitas Layanan Website Portal Jurnal Universitas Brawijaya dan Website Student Journal Universitas Brawijaya Menggunakan Metode Webqual 4.0 dan IPA (Importance Performance Analysis) - Okta Dwi Ariska; Ari Kusyanti; Fitra A. Bachtiar (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2018)
Brawijaya University has a website that is used to provide online journals that the user needs is the Journal Portal website and the Student Journal website. Based on the service (e-complaint) there are complaints from users of Portal Journal website that the user is difficult to login because the username and password are not integrated with the nim and password, and on the Student Journal website that is difficulty in uploading and there are menus that are not appropriate, This discusses the quality of service evaluation on Journal Portal website and Student Journal website using Webqual 4.0 and IPA (Importance Performance Analysis) method. The variables used in this research are Usability, Information Quality, and Service Interaction Quality. Data obtained based on the questionnaire that has been filled by 100 respondents who analyzed using IPA. Based on IPA quadrant analysis on Journal Portal website that needs to be improved that is statement which is located in quadrant I (Main Priority) and at quadrant III (Low Priority) that is U3, U4, SIQ21, and U5, U6, U7, SIQ17, SIQ18, SIQ19, SIQ20, SIQ19, SIQ20, SIQ20, SIQ20, SIQ20, SIQ20, SIQ20, SIQ20, SIQ20, SIQ20, SIQ20, SIQ20, SIQ18, SIQ20, SIQ21.